Constitution's peoples: a robust and group-centred interpretation of Section 35 of the Constitution Act, 1982, in light of R. v. Powley - Olthuis, Brent Brian (2005)
Since 1982. the Canadian Constitution has "recognized and affirmed the Aboriginal and treaty rights of the Indian, Inuit, and Métis peoples of Canada," peoples that hold their unique status within the federation by virtue of their prior social organisation. The author argues that, when Aboriginal rights are invoked, analysis should focus on the community in which the right is said to reside. Contemporary rights-holding communities are those linked to the normative orders that preceded and survived those of the later arrivals: in this regard, the Métis are not dissimilar from the other recognised Aboriginal peoples. It is the community's capacity to determine the norms applicable to its members' lives that is important, not the actual content of that order at a particular time: Aboriginal societies must be afforded the latitude to pursue their own aims and ambitions, and their rights must not be limited to activities that appear objectively 'Aboriginal".